Safety, tolerability, pharmacokinetics, and pharmacodynamics of the afucosylated, humanized anti-EPHA2 antibody DS-8895a: a first-in-human phase I dose escalation and dose expansion study in patients with advanced solid tumors - Kohei Shitara; Taroh Satoh; Satoru Iwasa; Kensei Yamaguchi; Kei Muro; Yoshito Komatsu; Tomohiro Nishina; Taito Esaki; Jun Hasegawa; Yasuyuki Kakurai; Emi Kamiyama; Tomoko Nakata; et al. (Journal for ImmunoTherapy of Cancer, 2019)
Abstract Background Erythropoietin-producing hepatocellular receptor A2 (EPHA2) is overexpressed on the cell surface in many cancers and predicts poor prognosis. DS-8895a is a humanized anti-EPHA2 IgG1 monoclonal antibody afucosylated to enhance antibody-dependent cellular cytotoxicity activity. We conducted a two-step, phase I, multicenter, open-label study to determine the safety, tolerability, and pharmacokinetics of DS-8895a in patients with advanced solid tumors. Methods Step 1 was a dose escalation cohort in advanced solid tumor patients (six dose levels, 0.1–20 mg/kg) to determine Step 2 dosing. Step 2 was a dose expansion cohort in EPHA2-positive esophageal and gastric cancer patients. DS-8895a was intravenously administered every 2 weeks for the duration of the study, with a 28-day period to assess dose-limiting toxicity (DLT). Safety, pharmacokinetics, tumor response, and potential biomarkers were evaluated. Results Thirty-seven patients (Step 1: 22, Step 2: 15 [9: gastric cancer, 6: esophageal cancer]) were enrolled. Although one DLT (Grade 4 platelet count decreased) was observed in Step 1 (dose level 6, 20 mg/kg), the maximum tolerated dose was not reached; the highest dose (20 mg/kg) was used in Step 2. Of the 37 patients, 24 (64.9%) experienced drug-related adverse events (AEs) including three (8.1%) with Grade ≥ 3 AEs. Infusion-related reactions occurred in 19 patients (51.4%) but were manageable. All patients discontinued the study (evident disease progression, 33; AEs, 4). Maximum and trough serum DS-8895a concentrations increased dose-dependently. One gastric cancer patient achieved partial response and 13 patients achieved stable disease. Serum inflammatory cytokines transiently increased at completion of and 4 h after the start of DS-8895a administration. The proportion of CD16-positive natural killer (NK) cells (CD3−CD56+CD16+) decreased 4 h after the start of DS-8895a administration, and the ratio of CD3−CD56+CD137+ to CD3−CD56+CD16+ cells increased on day 3. Conclusions Twenty mg/kg DS-8895a infused intravenously every 2 weeks was generally safe and well tolerated in patients (n = 21) with advanced solid tumors. The exposure of DS-8895a seemed to increase dose-dependently and induce activated NK cells. Trial registration Phase 1 Study of DS-8895a in patients with advanced solid tumors (NCT02004717; 7 November 2013 to 2 February 2017); retrospectively registered on 9 December 2013.